Risk factors and outcomes of postoperative extubation failure in children with fourth ventricular tumors: a case control study - Wenmin Yang; Jinda Huang; Feiyan Chen; Chunmin Zhang; Yiyu Yang (BMC Pediatrics)
Abstract Background and objective Microsurgical resection of tumor is an important treatment for children with fourth ventricular tumors. There is a lack of data describing risk factors for postoperative extubation failure (EF) in these children. We aimed to identify risk factors for EF in children with fourth ventricular tumors and to determine the association between EF and clinical outcomes. Methods A retrospective study review of children after fourth ventricular tumors surgery who had an extubation attempt between January 2020 to December 2023. Extubation failure was defined as re-intubation within 7 days of extubation. Multivariate logistic regression analysis was performed to explore the risk factors for EF. Bivariate statistical analysis was performed to determine associations between EF and clinical outcomes. Only the first extubation attempt was included in the analysis. Results We included 103 children, of whom 10 (9.7%) experienced EF. In the logistic regression analysis, a weak/absent cough reflex was independently associated with EF (p < 0.001). Compared to those with a fair/ strong cough, patients with a weak/absent cough had a odds ratio (OR) of 41.25 for EF (95% CI,8.01–212.37; p < 0.001).Glasgow Coma Score(GCS), the obvious adhesion between the tumor and the fourth ventricle floor, and pulmonary variables were not associated with EF. Children who failed extubation had longer durations of mechanical ventilation [13 days (IQR 6.8–22.8) vs. 1 days (IQR 0.5–3), p < 0.001]; longer PICU lengths of stay [16.5 days (IQR 9.4–27.5) vs. 2 days (IQR1.5–4.3), p < 0.001] and longer hospital lengths of stay [27 days (IQR 21–31.8) vs. 20 days (IQR16–29), p = 0.05] than successfully extubated children. Conclusions Children with weak/absent cough reflex after surgery are at increased risk for extubation failure. Extubation failure is associated with significant adverse outcomes in our setting.